ALIH KODE DAN CAMPUR KODE PADA NASKAH DRAMA KABAYAN MENCARI CINTA KARYA SALSABILA PIRIYANTI - Ria Suryani; Ian Sopian (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This article was created to analyze the languages used for dialogue in the contents of the manuscript entitled "Kabayan Mencari Cinta" by Salsabila Piriyanti. With code transfer and code mix, analyze the form of language transfer and interfere with the drama script "Kabayan Mencari Cinta" by Salsabila Piriyanti. Language is a communication tool or interaction tool that is only owned by humans, therefore defined as communication between humans, characterized by the use of symbols of oral or random symbols (arbitrary) according to the meaning that has been accepted. The method used in this research is descriptive qualitative method which means that this research analyze data and the result of the data in the form of description. From the analysis there are four languages used in the drama script "Kabayan Looking for Love" by Salsabila Piriyanti. Sample taken in this research is a character who is in Kabayan drama script looking for love that is: Kabayan, Neneng, Mba Putri, Abang Surya, Mba Anwa, Ivan, Mba Khansa, Euis, Iteung, Lilis, Abah Iteung and Mother Kabayan. And the language used, among others, Indonesian, Sundanese, Javanese and Betawi languages, in addition to find the phrases that are transfer code and mix code. There are ten codes and there are sixty-two mixed codes.